Restorative Justice as an Effort to Fulfill the Constitutional Rights of Citizens: Restorative Justice sebagai Upaya Pemenuhan Hak Konstitusional Warga Negara - Agustina, Vinda; Tisnanta, H. S.; Muhtadi, Muhtadi (Constitutional Court of the Republic of Indonesia, Indonesia, 2024)
This study aims to determine whether the settlement of criminal cases through restorative justice is an effort to fulfill the constitutional rights of citizens. The method used in this research is normative legal research with a statutory approach and a conceptual approach. The results of the study show that the settlement of cases through restorative justice is an effort to fulfill the constitutional rights of citizens because the principle of resolving cases through restorative justice can be said to be more able to guarantee justice and equality before the law (equality before the law) as regulated in Article 27 paragraph (1), Article 28D paragraph (1) and Article 28I paragraph (2) of the 1945 Constitution of the Republic of Indonesia.